Circulating microparticles: challenges and perspectives of flow cytometric assessment - Shantsila, Eduard; Montoro-García, Silvia; Gallego, Pilar; Lip, Gregory Y. H. (Thrombosis and Haemostasis, 2014)
Circulating blood microparticles are likely to play a significant role as messengers of biological information. Their accurate quantification and characterisation is challenging and needs to be carefully designed with preferable usage of fresh minimally-processed blood samples. Utilisation of flow cytometers specifically designed for analysis of small-size particles is likely to provide considerable methodological advantages and should be the preferable option. This viewpoint manuscript provides a critical summary of the key methodological aspects of microparticle analysis.Note: The review process for this viewpoint article was fully handled by Christian Weber, Editor in Chief.
Keywords: Microparticles; flow cytometry; microvesicles